1990
DOI: 10.1126/science.250.4983.967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climatic Warming on Lakes of the Central Boreal Forest

Abstract: Twenty years of climatic, hydrologic, and ecological records for the Experimental Lakes Area of northwestern Ontario show that air and lake temperatures have increased by 2 degrees C and the length of the ice-free season has increased by 3 weeks. Higher than normal evaporation and lower than average precipitation have decreased rates of water renewal in lakes. Concentrations of most chemicals have increased in both lakes and streams because of decreased water renewal and forest fires in the catchments. In Lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
250
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 407 publications
(267 citation statements)
references
References 25 publications
16
250
0
Order By: Relevance
“…In the Black Sea warm temperature and low wind stress can trigger unusually large blooms throughout the entire growing period (McQuatters-Gollop et al 2008). Similarly, increased wind stress, water temperature and reduced water run-off affected the phytoplankton dynamics in Boreal lakes (Schindler et al 1990).…”
Section: Phytoplankton Phenology As An Indicator Of Global Changementioning
confidence: 99%
“…In the Black Sea warm temperature and low wind stress can trigger unusually large blooms throughout the entire growing period (McQuatters-Gollop et al 2008). Similarly, increased wind stress, water temperature and reduced water run-off affected the phytoplankton dynamics in Boreal lakes (Schindler et al 1990).…”
Section: Phytoplankton Phenology As An Indicator Of Global Changementioning
confidence: 99%
“…The stratification process creates a potential for temperature differentials between deeper offshore and shallower near-shore subhabitats within a lake, as temperatures remain relatively constant in deep habitats, whereas shallower near-shore temperatures are strongly influenced by air temperatures (26). Monitoring in the boreal region (27,28) has shown that rising air temperature warms surface waters, accelerates the stratification process, and extends the duration of stratification; thus, air temperature is a primary determinant of lake thermal heterogeneity.…”
mentioning
confidence: 99%
“…Research on the relationship between climate change observed in the previous decades and aquatic food webs (Schindler et al 1990 Climate change can affect aquatic food webs in many ways. It can alter duration and timing of the successional status (Straile 2002), or modify the structure of the food web within different successional stages (Wehenmeyer et al 1999).…”
Section: Observed and Expected Reactions Of Aquatic Communitiesmentioning
confidence: 99%